2017
DOI: 10.1002/14651858.cd001188.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Nursing interventions for smoking cessation

Abstract: Editorial group: Cochrane Tobacco Addiction Group. Publication status and date: New search for studies and content updated (no change to conclusions), published in Issue 12, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(75 citation statements)
references
References 157 publications
5
65
0
1
Order By: Relevance
“…Our intervention could be too brief and inadequate to make an impact on such smokers. The results are also in-line with some previous reviews indicating that comprehensive intervention might be more effective than brief advice to promote smoking cessation 34 37 . However, providing comprehensive smoking cessation to cancer patients is not feasible in Hong Kong busy clinical settings, as in general, it takes more than 30 minutes to implement.…”
Section: Discussionsupporting
confidence: 90%
“…Our intervention could be too brief and inadequate to make an impact on such smokers. The results are also in-line with some previous reviews indicating that comprehensive intervention might be more effective than brief advice to promote smoking cessation 34 37 . However, providing comprehensive smoking cessation to cancer patients is not feasible in Hong Kong busy clinical settings, as in general, it takes more than 30 minutes to implement.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, antihypertensive and statin medications are associated with improvements in secondary prevention (Collins 2016; Ettehad 2016; Logue 2015; Preiss 2015; Sundström 2014;). Metaanalyses report that moderate to high physical activity (Bennett 2017; Fan 2017), moderate alcohol consumption (Holmes 2014; Reynolds 2003), reduction of salt intake (Aburto 2013; He 2013), and specific dietary changes (He 2004; He 2006) can also facilitate stroke prevention and cardiovascular risk reduction. An international case-control study identified five modifiable risk factors accounting for 83% of the population attributable risk (PAR) for stroke (O'Donnell 2010; Perk 2012).…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Staff education is an essential component of smoking cessation programmes and results in active engagement with smokers attending health care services [21,23], and should be fundamental in maternity care [27,31]. Campbell's study reiterates the importance of staff training in managing queries and engaging with pregnant women [40].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking cessation practices are fundamental for all health care professionals' interactions, as unequivocal evidence acknowledges that smoking cessation improves life expectancy and reduces the risk of chronic illness [1,[21][22][23]. The year 2015 overlapped with a 10-year review of the FCTC and an introduction of UN Sustainable Development Goals (SDGs) targets for 2030 [24].…”
Section: Introductionmentioning
confidence: 99%